Obesity and triple‐negative‐breast‐cancer: Is apelin a new key target? - Gourgue, Florian; Mignion, Lionel; Van Hul, Matthias; Dehaen, Natacha; Bastien, Estelle; Payen, Valery; Leroy, Baptiste; Joudiou, Nicolas; Vertommen, Didier; Bouzin, Caroline; Delzenne, Nathalie; Gallez, Bernard; et al. (Journal of cellular and molecular medicine, 2020)
Epidemiological studies have shown that obese subjects have an increased risk of developing triple‐negative breast cancer (TNBC) and an overall reduced survival. However, the relation between obesity and TNBC remains difficult to understand. We hypothesize that apelin, an adipokine whose levels are increased in obesity, could be a major factor contributing to both tumour growth and metastatization in TNBC obese patients. We observed that development of obesity under high‐fat diet in TNBC tumour‐bearing mice significantly increased tumour growth. By showing no effect of high‐fat diet in obesity‐resistant mice, we demonstrated the necessity to develop obesity‐related disorders to increase tumour growth. Apelin mRNA expression was also increased in the subcutaneous adipose tissue and tumours of obese mice. We further highlighted that the reproduction of obesity‐related levels of apelin in lean mice led to an increased TNBC growth and brain metastases formation. Finally, injections of the apelinergic antagonist F13A to obese mice significantly reduced TNBC growth, suggesting that apelinergic system interference could be an interesting therapeutic strategy in the context of obesity and TNBC.